Aging, Proximity to Death, and Religiosity. Issue 4 (24th August 2020) - Lechler, Marie; Sunde, Uwe
Abstract: Considerable evidence has documented that the elderly are more religious and that religiosity is associated with better health and lower mortality. Yet, little is known about the reverse role of life expectancy or proximity to death, as opposed to age, for religiosity. This paper provides evidence for the distinct role of expected remaining life years for the importance of religion in individuals' lives. We combine individual survey response data for more than 300, 000 individuals from 95 countries over the period 1994–2014 with information from period life tables. Contrary to wide‐held beliefs, religiosity decreases with greater expected proximity to death. The findings have important implications regarding the consequences of population aging for religiosity and associated outcomes.